Strategi Pemasaran Desa Budaya Kertalangu Sebagai Pusat Wisata Budaya - Ni Putu Limarandani (Cakrawala - Jurnal Humaniora, 2022)
Tourism is able to move the country's economy so that it brings in significant foreign exchange around the local tourism area. Kertalangu culture, which is located in Denpasar City, is among tourist areas that are well known throughout the world, such as the beaches of Sanur, Legian and others. This study explores information from informants through a qualitative research approach with a marketing strategy to promote the Kertalangu Cultural Village as a Balinese Cultural Tourism Center. Interviews with informants with internal and external interests by stating negative responses to marketing communications which include advertising, sales promotion, sales and public relations. Researchers only found one component of marketing communication that responded positively, namely direct marketing because it had been implemented by the manager of the Kertalangu Cultural Village. The researcher recommends a marketing communication strategy to improve tourism promotion, namely the efforts of internal and external stakeholders to increase awareness and loyalty of visitors/tourists of the Kertalangu Cultural Village and create a positive attitude towards the existence of cultural tourism created and offered by the Kertalangu Cultural Village. Visitors/tourists are refocused based on segmentation, targeting, and positioning. The marketing communication strategy that needs to be built is with an emphasis on the form of marketing communication in the form of advertising, promotion, personal selling and the use of social media that can reach various communities and geographical reach across national and regional boundaries